An analysis of service delivery protests and their implications on the economic stability of Musina Municipality: 2007-2014 - Phaswana, Rofhiwa (My University, 2018)
The adoption of the constitution in 1996 has opened a new era of establishing a local government system that recommended that municipalities be established for the whole territory of the republic of South Africa. The white paper on “Local Government adopted by Cabinet in March 1998 outlined framework and programmes to guide municipalities to commit to work with citizens and groups within the communities to find sustainable ways to meet their social, economic and material needs to improve the quality of their lives”. Since 2007 epidemic service delivery protests started to be a national problem where 80 percentages of service delivery protests between the periods of 2007-2014 were violent. For instance, Musina Municipality experienced violent service delivery during the period of 2007-2014 where its properties, economy and people’s lives were in stake. Therefore, this study was driven by the need to analyse the implications of service delivery protests on the economy of Musina Municipality. A qualitative method approach to investigate the problem of service delivery protests implications on stability and economy in Musina Municipality will be used. A case study regarding service delivery effectiveness and violence used by people as a response and expression of a plea to be heard by their municipality will be investigated.
MA (Political Studies)
Department of Political Studies
Keywords: Batho Pele principles; UCTD; Communication; Economy; Non-Compliance; Service delivery; Protests; 351.68257; Civil services -- South Africa -- Limpopo; Public utilities -- South Africa -- Limpopo; Municipal services -- South Africa -- Limpopo; Service at cost -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo